Coordinating construction logistics for multiple projects in an urban development district A case study of Masthuggskajen - BERG, MAGNUS; THORPÖ, CARL (My University, 2021)
Even with a continuous flow of studies proven its potential, construction logistics is an often-negligible part in the construction industry, particularly in dense cities. This thesis aims to investigate how the construction logistics plan in the project Masthuggskajen including adherent actors’ collaboration and logistics solutions contribute to the realization of Älvstranden Utveckling’s visions of Älvstaden. Through an abductive research process, both a literature study including topics of supply chain, supply chain management and construction coordination, as well as an empirical study including an interview- and an observational study, a holistic approach is taken on the current logistics situation. Contractors, project managers, and construction coordinators involved in project Masthuggskajen were interviewed. To guide the work, research questions encompass the collaboration in project Masthuggskajen and how it affects the coordination of construction logistics, how the current logistic plan is structured and adhered and what implementation of the logistics plan could benefit future projects are developed. The study shows that the current logistics mainly is individually coordinated in the different projects with a unified progress plan regulating the delivery routes. This progress plan is however not sufficiently adhered. Together with a decentralized view and focus on the individual project the common negative effects are overseen. Moreover, Älvstranden Utveckling needs to explicitly define their role towards the rest of the consortium to ensure the city of Gothenburg’s aims. They also need to develop the framework for representing and cooperating with the other local authorities. Finally, ensuring that information reaches throughout the supply chain down to the suppliers is shown as a success factor for a multi project district construction supply chain. This master thesis provides contributions for project Masthuggskajen in general and its coordination of construction logistics in particular by enlightening improvements and success factors to import to the eastern part of Masthuggskajen. To add a more comprehensive construction logistics solutions requirements into the land allocation agreements and an extended coordination is needed in future projects in Vision Älvstaden and other urban development districts with multiple projects
Keywords: Construction logistics; Construction coordination; Logistics solutions; Construction supply chain; Urban development